Penerapan Model Rais-Mr3 dalam Tata Kelola Transportasi Andalan di Sulawesi Selatan - Sirajuddin Sirajuddin; Muhammad Rais Rahmat Razak; Haeruddin Syarifuddin (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the effect of implementing the Rais-MR3 Model on the effectiveness of "ANDALAN" transportation governance in South Sulawesi Province. The Rais-MR3 Model consists of three main pillars: Accountability, Transparency, and Public Participation. The research method uses a quantitative approach with a causal associative design. The research population consisted of all parties involved in the implementation and utilization of "ANDALAN" transportation services, totaling 82 people who were selected as respondents using census technique. The research instrument was a Likert scale questionnaire that has been tested for validity (r count > 0.182) and reliability (Cronbach's Alpha = 0.968). Data analysis technique used simple linear regression with SPSS version 25. The results showed that all three pillars of the Rais-MR3 Model had positive and significant effects on transportation governance effectiveness. The Accountability pillar contributed 60.5% (R²=0.605; t=11.061; p<0.001), Transparency contributed 60.4% (R²=0.604; t=11.050; p<0.001), and Public Participation had the greatest influence at 72.6% (R²=0.726; t=14.557; p<0.001). The overall implementation of the Rais-MR3 Model contributed 76.9% (R²=0.769; t=16.335; p<0.001), demonstrating a strong synergistic effect. These findings prove that a holistic approach through the integration of accountability, transparency, and public participation can significantly improve the effectiveness of regional public transportation governance. Theoretically, this study reinforces the relevance of the New Public Service paradigm in the context of regional public transportation governance, while providing policy implications for local governments to adopt participatory and accountability-based governance approaches as a strategy for sustainable public service improvement.